2018
DOI: 10.1002/bdm.2105
|View full text |Cite
|
Sign up to set email alerts
|

Is the DOSPERT gender invariant? A psychometric test of measurement invariance

Abstract: It is well established in the risk literature that men tend to take more risks than women. This gender difference, however, is often qualified by its domain specificity. Considering recent research on the domain generality of risk taking as a disposition, there is a need to examine the degree to which men take more risks than women, in general. In order to make substantive conclusions about the gender differences in risk‐taking propensity, one must first establish measurement invariance, which is required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
1
13
1
Order By: Relevance
“…This finding suggests that domain specificity in perceptions of risks and benefits may have been exaggerated—in terms of dissociations across risk domains—in previous studies with the DOSPERT. Recently, researchers have questioned the extent of domain specificity in risk taking behavior (Frey, Pedroni, Mata, Rieskamp, & Hertwig, ; Highhouse et al, ; Zhang, Foster, & McKenna, ). Frey et al () assessed individual differences in risk taking across 39 measures of risk preference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding suggests that domain specificity in perceptions of risks and benefits may have been exaggerated—in terms of dissociations across risk domains—in previous studies with the DOSPERT. Recently, researchers have questioned the extent of domain specificity in risk taking behavior (Frey, Pedroni, Mata, Rieskamp, & Hertwig, ; Highhouse et al, ; Zhang, Foster, & McKenna, ). Frey et al () assessed individual differences in risk taking across 39 measures of risk preference.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings indicate that apparent gender differences in risk taking can be highly dependent on the specific items selected to represent a risk domain. Moreover, Zhang, Foster, and McKenna (2019) found that the underlying factor structure of the DOSPERT differs for men and women, which raises additional concerns about the assessment of gender differences in self-reported risk taking on the DOSPERT.…”
Section: Gender Differences In Risk Perception Expected Benefit Amentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings indicated that in the social domain, women perceived greater risk than men; in other words, they had a lower tolerance for risk. On the other hand, Zhang et al (2019) pointed out that risk-taking in the social domain functions differently across groups. Furthermore, other authors have argued that there is a gender confirmation bias in risk-taking due to its traditional association with stereotypically masculine activity (Morgenroth et al, 2018), which could affect women's behavior.…”
Section: Femininity Fear Of Negative Evaluation and Risk-takingmentioning
confidence: 99%
“…The literature has indicated that women rate themselves more likely to make risky decisions in the social domain (e.g., Figner and Weber, 2011). Nevertheless, there is controversy around this finding (Zhang et al, 2019), which may cause confusion because people who identify themselves as more feminine -traditionally women -are conditioned to be more cautious, whereas those who identify themselves as more masculine -traditionally men -are conditioned to be riskier (Carver et al, 2013). In this sense, the social domain (e.g., "speaking your mind about an unpopular issue in a meeting at work" or "moving to a city far away from your extended family") is a context in which women could experience more FNE if they were to make risky decisions, given that they would deviate from their traditional role (Rudman et al, 2012).…”
Section: The Current Researchmentioning
confidence: 99%